Modern control systems / Richard C. Dorf, Robert H. Bishop - Dorf, Richard C.; Bishop, Robert H. 1957- (Pearson, 2017)
This text is designed for an introductory undergraduate course in control systems for engineering students.There is very little demarcation between aerospace, chemical, electrical, industrial, and mechanical engineering in control system practice: therefore this text is written without any bias towards one particular discipline. Thus, this book will be equally useful for all engineering disciplines and, perhaps, will assist in illustrating the utility of control engineering as a controlled discipline.